2006
DOI: 10.1074/jbc.m506933200
|View full text |Cite
|
Sign up to set email alerts
|

erbB1 Functions as a Sensor of Airway Epithelial Integrity by Regulation of Protein Phosphatase 2A Activity

Abstract: Two enzymes, protein phosphatase 2A and atypical protein kinase C, are associated with the tight junction and regulate its function. For example, phosphorylation of the tight junction protein occludin is required for its incorporation into the junction. The association of a kinase and phosphatase with the tight junction suggests that a balance between their activities exists and is required for normal tight junction function. This hypothesis predicts that loss of epithelial integrity may disrupt this balance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In MDCK cells overexpressing the catalytic subunit of PP2A, recruitment of PKC ζ to junctional complexes was impaired during TJ biogenesis [106]. In pulmonary adenocarinoma Calu-3 cells, Vermeer et al [108] showed a similar complex formation between PP2A and occludin, claudin-1 and aPKC λ at the cell junctions and dissociation of PP2A from occludin and claudins when TJs are disintegrated. Disruption of TJs is a prerequisite for apically secreted EGF ligands to activate their basolateral receptors [109].…”
Section: Phosphatases Counteracting Occludin Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In MDCK cells overexpressing the catalytic subunit of PP2A, recruitment of PKC ζ to junctional complexes was impaired during TJ biogenesis [106]. In pulmonary adenocarinoma Calu-3 cells, Vermeer et al [108] showed a similar complex formation between PP2A and occludin, claudin-1 and aPKC λ at the cell junctions and dissociation of PP2A from occludin and claudins when TJs are disintegrated. Disruption of TJs is a prerequisite for apically secreted EGF ligands to activate their basolateral receptors [109].…”
Section: Phosphatases Counteracting Occludin Phosphorylationmentioning
confidence: 99%
“…Disruption of TJs is a prerequisite for apically secreted EGF ligands to activate their basolateral receptors [109]. Concomitant with an EGF-induced tyrosine phosphorylation of the PP2A catalytic subunit, PP2A is inactivated allowing phosphorylation of aPKC and its translocation to tight junctional complexes thus promoting assembly [106, 108]. Under inflammatory conditions, which were simulated by TNF α /IFN γ treatment, junctional integrity was compromised leading to a drop in TER which was reverted in the presence of ocadaic acid [108].…”
Section: Phosphatases Counteracting Occludin Phosphorylationmentioning
confidence: 99%
“…Conversely, airway epithelia may provide an important "watchtower" function by amplifying inflammation when the airway mucosal barrier is breached. This could explain the paradoxical observation that selected inflammatory mediators may directly lower airway epithelial barrier function, as has been demonstrated when histamine, protease-activated receptor 2-activating peptide, or both TNF-␣ and IFN-␥ are applied to the basolateral surface (18,25,42,49).…”
Section: Discussionmentioning
confidence: 99%
“…6). These mechanisms include the dysregulation of signaling through ErbB receptors that are constitutively expressed on nasal epithelium [67,68,69], leading to the degradation of tight junction proteins and widening of intercellular spaces, consistent with the pathological features of NAVMR. Additionally, the dysregulation of ciliary protein expression and mucin oversecretion in NAVMR is implied by CDA-induced under-expression of miR-449 with a consequent lack of Notch signaling control [5,70,71] (Fig.…”
Section: Discussionmentioning
confidence: 99%